The missing mission in health - Dasgupta, Rajib; Bisht, Ramila (2010)
The National Urban Health Mission was supposed to address the unmet health needs of urban Indians. Yet, it has failed to commence work even 18 months after the announcement of its formation. A rapidly urbanising India has been marked by a series of epidemics of communicable diseases in the last two decades and increasing informalisation of the economy. Urban health systems, therefore, need serious and quick reforms. - Reproduced.
Keywords: Health services - India; Health services